Analysis and Evaluation of Effect of Manganese Content on Properties of EN AC 46000 Aluminum Alloy - Pasternak, Martyna; Brzeziński, Marcin; Piwowarczyk, Gabriela (Journal of Casting & Materials Engineering, 2019)
This article is the effect of industrial work and many surveys in the one of the Polish foundries that specialize in aluminum alloys. The main goal of our explorations is to evaluate the influence of manganese on Al-Si alloy properties. In die-cast alloys, it is recommended to use larger amounts of iron to reduce the impact on the pressure chamber and mold. Manganese neutralizes the harmful effect of iron by changing the morphology of the separated brittle ferrous phases. The unfavorable form of the iron-containing phases in the form of long needles changes into the forms of fine compact crystals, which are less harmful to the mechanical properties. Nowadays, the main client requirement is to obtain the right parameters at the best price. Specifically, the customer is in the automotive industry, where new technologies provide a connection between the high quality and low weight of car parts [1–3].